Three dimensional dynamical model of finswimming - Baly, L.; Chavet, P.; Berton, E.; Favier, D. (2002)
The purpose of this study is to develop and to validate a 3D numerical model which allow the accurate description of the elite finswimmers movement and which provide an optimization of the swimming technique. Such an approach links kinematics analysis methods [1] performe in a real situation with experimental measurements performed in a wind-tunnel [2]. RESULTS Differences between men and women have been exhibited in both temporal and spatial domains. Although undulatory frequency are quite similar for boths sexes, swimming velocity and range of movement are shown to be smaller for women than for men. Moreover, such frequency and completed parameters are adjusted to race distance. The undulatory swimmer movement starts from hands and propagates along the body, with an important part provided by knee and ankle which are strongly correlated. A phase relation was clearly observed between frequency and range of undulation. The kinematics data were used to define the accurate monofin geometry and its angle of attack with respect to the flow conditions in the wind-tunnel. Numerical results obtained on the body joints efforts at different phases of the swimmer motion have shown to be consistent with previous literature data obtained by means of water tunnel simulating. Moreover the present numerical model using the external forces as determined from the wind-tunnel simulation, has also shown in higher degree of accuracy in predicting the swimmer dynamical performances when compared to previous studies by the same group [1].